MONITORING OF SPECIES DIVERSITY OF NON-TUBERCULOSIS MYCOBACTERIA IN THE SOME RUSSIAN REGIONS USING DNA-STRIPS OF GENOTYPE MYCOBACTERIUM CM/AS (HAIN LIFESCIENCE, GERMANY) - T. G. Smirnovа; S. N. Аndreevskаya; E. E. Lаrionovа; I. Yu. Аndrievskаya; V. V. Ustinovа; L. N. Chernousovа (Туберкулез и болезни лёгких, 2017)
Goal of study: to define species of non-tuberculosis mycobacteria, isolated from the respiratory tract of the patients from various Russian regions using DNA strips for identification of non-tuberculous mycobacteria.Materials and methods. 1204 cultures of non-tuberculosis mycobacteria isolated on solid and liquid media from 727 patients in whom tuberculosis/mycobacteriosis was suspected were examined from 2011 to February, 2017. Species of non-tuberculosis mycobacteria were identified using DNA-strips of Hain Lifescience (Germany) GenoType® Mycobacterium CM/AS in compliance with manufacturer's instructions.Results. 17 species of non-tuberculosis mycobacteria were identified (11 species belonged to the group of those slow-growing and 6 species belonged to fast growing non-tuberculosis mycobacteria). Slow-growing mycobacteria prevailed (564/727, 77.58%) and M. avium was the most prevalent (210/727; 28.89%). The following mycobacteria were found (in descending order): M. gordonae (99/727; 13.62%), M. intracellulare (68/727; 9.35%), M. lentiflavum and M. fortuitum (по 66/727; 9.08%), M. abscessus (49/727; 6.74%), M. kansasii (48/727; 6.60%), M. xenopi (29/727; 3.99%). Prevalence of non-tuberculosis mycobacteria is described in respect of the regions.